Manganese status in upland and lowland rubber-growing soils in Songkhla province, southern Thailand - Siskawardani, Devi Dwi; Onthong, Jumpen; Khawmee, Khwunta; Poonpakdee, Chakkrit (Agriculture and Natural Resources, 2016)
Rubber trees, the most economic crop in southern Thailand, are generally cultivated in acid upland soils and currently have been extended into lowland areas which induce higher solubility of manganese (Mn) which may result in Mn toxicity to rubber. This study investigated soil Mn and leaf Mn levels in rubber trees grown in upland and lowland soils. Ninety soil samples from upland and lowland rubber plantations in Songkhla province were collected and analyzed for water soluble Mn, NH4OAc Mn, diethylenetriaminepentaacetic acid test (DTPA) Mn, reducible Mn and total Mn forms. Leaf Mn analysis was also undertaken on samples of each plantation. The results revealed that the Mn concentrations of all soil Mn forms and leaf Mn in the lowland soils were higher than those of the upland samples. Comparing the optimum level reported by the Rubber Research Institute, both DTPA Mn and leaf Mn in the upland and lowland samples were high. Correlation analysis showed high and significant positive correlations of DTPA Mn and water Mn (r = 0.715), NH4OAc Mn (r = 0.975), reducible Mn (r = 0.953) and total Mn (r = 0.809) in the lowland samples. Medium to high positive correlations among Mn forms were also found in the upland samples. The correlation of soil properties (pH, electrical conductivity, organic matter, available K, exchangeable Ca, Mg and Na and cation exchange capacity) and soil Mn were clearly defined. These results indicated that soil properties affect the release of Mn. However, a correlation between soil Mn and leaf Mn was not observed.